Labour market and education reforms are needed to create more and better jobs in Türkiye - Dlugosch, Dennis (OECD Publishing, 2023)
The Turkish economy grew strongly over the past two decades and created many jobs. However, given its young and growing workforce, Türkiye needs to ramp up efforts to achieve high-quality formal job creation. A sizeable share of the workforce, mostly female workers, does not actively participate in the labour market. While informality has decreased significantly, it is still widespread and entrenches productivity differences across firms. Rigid labour market rules, particularly the high severance pay but also minimum wages, impede formal job creation. More flexible labour markets should be part of a comprehensive reform programme that shifts job loss protection to a broader-based unemployment insurance scheme, supported by well-designed activation policies. While educational attainment has risen impressively, a growing number of vacancies, significant skill mismatches and a low level of adult skills highlight the need to address the quality of education and to improve on the matching of talent to jobs
Keywords: Economics; Türkiye